STRATEGI PROMOSI RUMAH MAKAN SAUNA ALAM PRATAMA DALAM MENARIK MINAT PELANGGAN - Ramadhan, Mohammad Rizki (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
The purpose of this research is to determine the promotional strategy carried out by the Alam Pratama Sauna Restaurant to attract customer interest. The type of research used is qualitative descriptive type. The basis of research in this research is a case study with a total of 3 informants, the data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions or verification. The results of the research show that in culinary business competition in the city of Palu, Rumah Makan Sauna Alam Pratama carries out a promotion strategy with interactive marketing/internet marketing via social media Instagram by integrating features such as followers, photo uploads, captions. photos), Instagram stories, Geotagging, Arroba 16, Social networking for sharing photos or videos, Likes, Comments, Instagram camera, Photo effects. Apart from that, Alam Pratama Sauna Restaurant uses Word of Mouth media. In carrying out this promotional strategy, Alam Pratama Sauna Restaurant uses internet marketing as a promotional media, apart from being cheap and easy to use, this media is very effective for spreading promotional information.